KONSEP DASAR KURIKULUM PENDIDIKAN AGAMA ISLAM - Abdul Wafi (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2017)
The study aimed to determine (1) Learning Auditory Intellectually Repetition (AIR) model on student’s problem solving abilities environmental material. (2) Expository model teaching on student’s problem solving abilities environmental material. (3) The difference between AIR and expository teaching model on student’s problem solving abilities and environmental material is better between the two. The population in this study were students of class XI-IPS SMA Negeri 2 Brebes. The samples taken at random sampling with XI-IPS 1 as an experimental class and XI-IPS 2 as a control class. The study design used was quasy experimental with posttest-only control design.